EXTENDED THEORY OF PLANNED BEHAVIOR AS MODEL OF ANABOLIC ANDROGENIC STEROID USE BY INDONESIAN BODYBUILDERS - Shine Pintor Siolemba Patiro; Basu Swastha Dharmmesta; Sahid Susilo Nugroho; Bayu Sutikno (Journal of Indonesian Economy and Business (JIEB), 2016)
This correlational study explored the psychological antecedents of Indonesian bodybuilders’ intentions to use anabolic–androgenic steroids (AAS), based on the Theory of Planned Behavior (TPB). The purpose of this research was to identify factors that influence an Indonesian bodybuilder’s intention to use AAS and offer a better understanding of AAS use behavior based on the extended Theory of Planned Behavior (TPB). The three predictor variables of (1) attitude, (2) subjective norms, and (3) perceived behavioral control accounted for the variation in the outcome measure of the intention to reuse the AAS. Likewise, (1) attitude and (2) intention accounted for of the variation in the outcome measure of the reuse of AAS. This research combined two methods which are qualitative and quantitative. The respondents who were used in this research are professional bodybuilders located in Jakarta, Bandung, Surabaya, and Yogyakarta. The result of this research shows that the attitude of bodybuilders in using AAS tends to have values that are adopted by themselves. The result of this research differs from Bagozzi et al (1989) who stated that attitude influenced behavior directly as a nonpurposeful reaction or indirectly through intention as an aimed response. The result of this research clearly shows that attitude can influence behavior directly as a purposeful reaction, because the bodybuilders consume AAS to achieve a particular purpose and it is strengthened by achievement value in themselves. This research suggests also that attitude and subjective norms are not causally independent. They appear to reflect similar beliefs and to influence each other. These results differ from Titah and Barki (2009), as suggested by Chang (1998) and Aarts et al. (1998), who stated that a person whose positive subjective norms move them toward overt behavior, it will lead to a positive attitude toward the behavior. Future research directions are suggested regarding several areas.Keywords: Theory of Planned Behavior; values; steroid; bodybuilders